Association between serum magnesium and blood lipids: influence of type 2 diabetes and central obesity. Issue 3 (23rd May 2018) - Yu, Lianlong; Zhang, Junli; Wang, Liansen; Li, Suyun; Zhang, Qian; Xiao, Peirui; Wang, Kebo; Zhuang, Maoqiang; Jiang, Ying
Abstract: To assess the changes in the relationship between serum Mg and blood lipids of Chinese adults with type 2 diabetes (T2D) or central obesity, a total of 8163 subjects (mean age 59·6 years, 54·9 % men) were analysed. Participants were classified according to blood Mg (below 0·65 mmol/l, 0·65–0·95 mmol/l and above 0·95 mmol/l), T2D (yes/no) and central obesity (yes/no). Blood lipids (TAG, total cholesterol (TC), HDL-cholesterol and LDL-cholesterol) were determined by standardised methods and conditions. A significant increase in blood lipids, with the exception of HDL-cholesterol, across progressive Mg groups in all subjects was noted ( P <0·05). TAG, TC, HDL-cholesterol and LDL-cholesterol were significantly higher among subjects with central obesity compared with those without central obesity ( P <0·05). A significant increase in TAG, TC and LDL-cholesterol across progressive Mg groups was observed in subjects without T2D ( P <0·05). However, no significant change of HDL-cholesterol and LDL-cholesterol across progressive Mg groups was observed in subjects with T2D ( P >0·05). TAG, TC, HDL-cholesterol and LDL-cholesterol were significantly higher among subjects with T2D than those without T2D ( P <0·05). Multivariable models for TAG and LDL-cholesterol failed to attain statistical significance in diabetics, by using a generalised linear or parsimonious model. TAG, TC, HDL-cholesterol and LDL-cholesterol were significantly higher among subjects with T2D or central obesity. Blood lipids, with the exception of HDL-cholesterol, were associated with serum Mg, but this association was somehow influenced by T2D in LDL-cholesterol. In addition, multivariable models for both TAG and LDL-cholesterol failed to attain statistical significance among subjects with T2D, different from subjects without T2D.